Pregunta
upstudy study bank question image url

Express the given function \( h \) as a composition of two functions \( f \) and \( g \) so that \( h(x)=(f \circ g)(x) \), where one of the functions is \( x^{4}-3 \). \( h(x)=\sqrt[7]{x^{4}-3} \) \( f(x)=x^{6} \) (Simplify your answer.)

Ask by Colon Daniels. in the United States
Feb 25,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

\( g(x) = x^{4} - 3 \) and \( f(x) = x^{\frac{1}{7}} \).

Solución

We want to write   h(x) = √[7](x⁴ – 3) = (x⁴ – 3)^(1/7) as a composition of two functions f and g where one of the functions is x⁴ – 3. A natural choice is to let   g(x) = x⁴ – 3              (choose the given expression for g) and then choose f so that   f(g(x)) = (g(x))^(1/7). In other words, we let   f(x) = x^(1/7). Then the composed function is   (f ∘ g)(x) = f(g(x)) = (x⁴ – 3)^(1/7) = h(x). (Note: Although the problem statement also listed f(x) = x⁶, this value does not produce h(x) when composed with g(x) = x⁴ – 3. The correct choice here is f(x) = x^(1/7).) Thus, the answer is:   g(x) = x⁴ – 3  and  f(x) = x^(1/7).

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Extra Insights

To express the function \( h(x) = \sqrt[7]{x^{4}-3} \) as a composition of two functions, where one of the functions is \( x^{4} - 3 \), we can identify \( g(x) = x^{4} - 3 \) and then define \( f(x) \) based on the output of \( g(x) \). Now, using the definition of \( f \) given as \( f(x) = x^{6} \), we can rewrite \( h \): 1. \( g(x) = x^{4} - 3 \) 2. Since we need to take the seventh root of \( g(x) \) for \( h(x) \), which is equivalent to raising \( g(x) \) to the power of \( \frac{1}{7} \), we define: \( f(y) = y^{\frac{1}{7}} \) for \( y = g(x) \). Now we combine them to represent \( h(x) \): \[ h(x) = f(g(x)) = f(x^{4} - 3) = (x^{4} - 3)^{\frac{1}{7}} \] Thus, we can present the composition as: \[ h(x) = f(g(x)) \quad \text{where} \quad g(x) = x^{4} - 3 \quad \text{and} \quad f(y) = y^{\frac{1}{7}}. \] So, \( (f \circ g)(x) = (x^{4} - 3)^{\frac{1}{7}} \).

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad